2018
DOI: 10.1002/ecj.12117
|View full text |Cite
|
Sign up to set email alerts
|

Development of micro‐inclined well array for trapping single cells

Abstract: We investigated the shape of a well to trap single cells for the purpose of improving the cell trapping rate after cell seeding and liquid exchange in a cell microarray. The wells having vertical and inclined tapered side‐wall were made using three‐dimensional UV photolithography. Changes in cell trapping rate by the shape of the wells were evaluated by trapping tests with fluorescent microbeads and living cells. As a result of trapping test with living cells, bead residual rate of the microarray with inclined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…29) After SU-8 cooling, the PDMS mold and the substrate are separated. After that, UV light is exposed with a normal exposure dose for an SU-8 submillimeter thickness from the back side of the Cr-patterned glass substrate 30) [Fig. 3(i)].…”
Section: Fabrication Processmentioning
confidence: 99%
“…29) After SU-8 cooling, the PDMS mold and the substrate are separated. After that, UV light is exposed with a normal exposure dose for an SU-8 submillimeter thickness from the back side of the Cr-patterned glass substrate 30) [Fig. 3(i)].…”
Section: Fabrication Processmentioning
confidence: 99%
“…The two-dimensional geometry of a conventional well fabricated using photolithography is flexible in design [ 29 , 30 , 31 ]. In contrast, we propose an SCM with inverse-tapered three-dimensional (3D) wells (fabricated via 3D photolithography) to achieve single-cell immobilization and prevent cell dropout during the liquid exchange [ 32 ]. We carried out immobilization experiments with protoplasts of single plant cells with a mean diameter of 30 μm and found that the inverse-tapered wells contributed to a higher cell residual rate after one wash than the vertical wells.…”
Section: Introductionmentioning
confidence: 99%
“…38 Among these techniques, microfluidic arrays have been most commonly applied for their ability to simultaneously immobilize many single cells and enable in situ observation over time. 9 However, their complicated fabrication and the associated expense of photolithography and soft lithography have hindered the commercialization of these chips. 10,11 In addition, most of the trapped cells are always kept in round traps, which might influence their cellular functions.…”
Section: Introductionmentioning
confidence: 99%
“…In the analysis of single cells, to prevent interference from cell–cell interaction, trapping or immobilizing individual cells is a fundamental task. Numerous techniques have been developed to create microarrays that can trap single cells, based on the guidance of optical, magnetic, electrical, centrifugation, ultrasonic, pressure, and hydrodynamic forces. Among these techniques, microfluidic arrays have been most commonly applied for their ability to simultaneously immobilize many single cells and enable in situ observation over time . However, their complicated fabrication and the associated expense of photolithography and soft lithography have hindered the commercialization of these chips. , In addition, most of the trapped cells are always kept in round traps, which might influence their cellular functions.…”
Section: Introductionmentioning
confidence: 99%